Respuesta :
Answer:
m = -7
Step-by-step explanation:
5m+8(1+8m)=−475
5m+(8)(1)+(8)(8m)=−475
m+8+64m=−475
(5m+64m)+(8)=−475
69m+8=−475
69m+8=−475
69m+8−8=−475−8
69m=−483
69m/69= −483/69
Answer:
[tex] \boxed{ \bold{ \huge{ \boxed{ \text{m = - 7}}}}}[/tex]
Step-by-step explanation:
[tex] \star{ \text{ \: 5m + 8(1 + 8m) = - 475}}[/tex]
[tex] \text{ \text{Step \: 1 \: : Distribute \: 8 \: through \: the \: parentheses}}[/tex]
[tex] \hookrightarrow{ \sf{5m + 8 + 64m = - 475}}[/tex]
[tex] \text{Step \: 2 \: : \: Collect \: like \: terms}[/tex]
[tex] \text{Like \: term \: are \: those \: which \: have \: the \: same \: base}[/tex]
[tex] \hookrightarrow{ \sf{69m + 8 = - 475}}[/tex]
[tex] \text{Step \: 3 \: : Move \: 8 \: to \: right \: hand \: side \: and \: change \: its \: sign}[/tex]
[tex] \hookrightarrow{ \sf{69m = - 475 - 8}}[/tex]
[tex] \text{step \: 3 \: : Calculate}[/tex]
[tex] \text{ \underline{Remember !}} \: : \text{The \: negative \: integers \: are \: always \: added \: but \: posses \: te \: negative \: ( \: - \: ) \: sign}[/tex]
[tex] \hookrightarrow{ \sf{69m = - 483}}[/tex]
[tex] \text{ Step \: 4 \: : Divide \: both \: sides \: by \: 69}[/tex]
[tex] \hookrightarrow{ \sf{ \frac{69m}{69} = \frac{ - 483}{69}}} [/tex]
[tex] \text{ Step \: 5 \: : Calculate}[/tex]
[tex] \hookrightarrow{ \sf{m = - 7}}[/tex]
[tex] \text{Hope \: I \: helped !!} [/tex]
[tex] \text{Best \: regards !!}[/tex]
~[tex] \sf{TheAnimeGirl}[/tex]